Food plant diversity determines home range area and formation of a new family group of the world’s rarest primate - Wang, Lu; Li, Yousheng; Cui, Jie; Zhang, Hui; Gong, Wenfeng (Frontiers in Environmental Science, 2022)
Global primates are endangered, and thus it is important to know the determinants of primate population dynamics. It is widely reported that food plant diversity and nutrients are key determinants of many primate population dynamics. However, it remains unknown whether this can be applied to explain the population dynamics of Hainan gibbon (Nomascus hainanus), the world’s rarest primate. Recently, two individuals moved out from one family group (group C) and went across more than 9 km to form a new family group (group E), thus providing a perfect chance to quantify whether food plant diversity and nutrients can determine Hainan gibbon’s formation of the new family group. Here, we used a plot survey to compare the differences in food plant diversity (species richness and abundance) and nine leaf nutrient traits (leaf water content, total soluble sugar, vitamin C, calorific value, crude fat, crude protein, crude fiber, Zn, and Fe) between group C and group E. We found that plant diversity in group E was indeed higher (1.35–1.41 times) than that in group C. Moreover, in both groups C and E, food plant diversity within the home range was also higher (1.4–1.6 times) than that out of the home range. However, both cases could not be witnessed for all leaf nutrient traits. Results of principal component analysis revealed that food plant species between groups C and E were all significantly separated by food plant diversity but not leaf nutrient traits. Food plant species within and out of the home range of both groups C and E could also be significantly separated by food plant diversity, but not for all leaf nutrient traits. In conclusion, food plant diversity was one key determinant of the formation of a new family group of Hainan gibbons. Choosing high food plant diversity was also one key motivation for Hainan gibbons to select their home range.